2017
DOI: 10.1038/mp.2017.189
|View full text |Cite
|
Sign up to set email alerts
|

Genetic contributions to Trail Making Test performance in UK Biobank

Abstract: The Trail Making Test (TMT) is a widely used test of executive function and has been thought to be strongly associated with general cognitive function. We examined the genetic architecture of the TMT and its shared genetic aetiology with other tests of cognitive function in 23 821 participants from UK Biobank. The single-nucleotide polymorphism-based heritability estimates for trail-making measures were 7.9% (part A), 22.4% (part B) and 17.6% (part B − part A). Significant genetic correlations were identified … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…However, there is evidence that performance in the TMT is related primarily to processing speed and working memory ability, as well as fluid intelligence (Sánchez-Cubillo et al, 2009; Satterthwaite et al, 2013). These findings are supported by evidence of genetic correlations between trail-making performance, reasoning ability and general cognitive ability, processing speed, and memory (Hagenaars et al, 2018). Research has also found differences between the cognitive processes underlying TMT-A and B performance.…”
Section: Discussionmentioning
confidence: 74%
“…However, there is evidence that performance in the TMT is related primarily to processing speed and working memory ability, as well as fluid intelligence (Sánchez-Cubillo et al, 2009; Satterthwaite et al, 2013). These findings are supported by evidence of genetic correlations between trail-making performance, reasoning ability and general cognitive ability, processing speed, and memory (Hagenaars et al, 2018). Research has also found differences between the cognitive processes underlying TMT-A and B performance.…”
Section: Discussionmentioning
confidence: 74%
“…It is often said to be an assessment of executive function. Though not considered a classical test of intelligence, Trails B performance is genetically and phenotypically strongly related to general intelligence as well as the cognitive domain of processing speed (Hagenaars, Cox, Hill, Davies, & Liewald, 2018; MacPherson et al, 2017; MacPherson, Allerhand, Cox, & Deary, 2019; Salthouse, 2011). In part B, participants were presented with the numbers 1–13, and the letters A-L arranged quasi-randomly on a computer screen.…”
Section: Methodsmentioning
confidence: 99%
“…Owing to positively skewed distributions, both TMT A and TMT B scores were log-transformed prior to further analyses. Further detail on these tests in UK Biobank has been published previously [ 43 ]. Processing speed was measured using the symbol digit substitution test, similar to the well-validated Symbol Digits Modalities Test [ 44 ], which was also part of the follow up testing wave.…”
Section: Methodsmentioning
confidence: 99%